Astronomy for Educators - Barth, Daniel E. (Open textbook library., 2018)
Astronomy for Educators provides new and accomplished K-12 instructors with concepts and projects for low-cost, high-impact STEM classroom instruction that is built around the National Academies National Research Council's K-12 Framework for Science Education.